Zmiany drzewostanów Białowieskiego Parku Narodowego w okresie 2000–2015 - Miścicki, Stanisław (Leśne Prace Badawcze, 2016)
The aim of the study was to characterise changes in the natural forest of the Białowieża National Park (BNP) Strict Reserve during a 15-year period. To allow for a more precise determination of the time course, overall duration and intensity of the observed changes, we further divided the 15-year period into shorter 2–7-year intervals. Taken together, the Strict Reserve forest stands cover 4584 hectares and they constitute the oldest part of the Białowieża Forest placed under protection in 1921. The measurements were carried out in 2000, 2002, 2004, 2011 and 2015 on 160 permanent sample plots, which are systematically distributed throughout the BNP Strict Reserve. During those 15 years, the volume of merchantable timber and the tree density fluctuated only slightly, because the reduction in standing volume due to a spruce and ash decline was compensated for by an increase in the standing volume of lime, hornbeam and alder. The volume increment and tree loss fluctuated slightly, but were nevertheless similar throughout the whole period between 2000 and 2015. The number of trees in the regeneration layer increased. The number of hornbeam trees in this layer increased continuously throughout the whole measurement period, while the number of maple trees started to increase in the second half. All together only five tree species growing in the BNP Strict Reserve progressed from the regeneration layer to the canopy layer in significant numbers. As a result, a gradual decrease in species diversity of forest stands may be expected. The rather stable, average volume of merchantable timber in the BNP Strict Reserve may be due to the fact that, in a forest with diverse habitats and high species richness, only few stands are subjected to strong disturbances in a given period of time. Repeated measurements during a relatively short period of time allowed the detecting some fairly quick changes occurring in natural lowland forests.